Hospital-acquired influenza in the United States, FluSurv-NET, 2011–2012 through 2018–2019. (5th October 2022) - Cummings, Charisse N.; O'Halloran, Alissa C.; Azenkot, Tali; Reingold, Arthur; Alden, Nisha B.; Meek, James I.; Anderson, Evan J.; Ryan, Patricia A.; Kim, Sue; McMahon, Melissa; McMullen, Chelsea; Spina, Nancy L.; et al.
Abstract: Objective: To estimate population-based rates and to describe clinical characteristics of hospital-acquired (HA) influenza. Design: Cross-sectional study. Setting: US Influenza Hospitalization Surveillance Network (FluSurv-NET) during 2011–2012 through 2018–2019 seasons. Methods: Patients were identified through provider-initiated or facility-based testing. HA influenza was defined as a positive influenza test date and respiratory symptom onset >3 days after admission. Patients with positive test date >3 days after admission but missing respiratory symptom onset date were classified as possible HA influenza. Results: Among 94, 158 influenza-associated hospitalizations, 353 (0.4%) had HA influenza. The overall adjusted rate of HA influenza was 0.4 per 100, 000 persons. Among HA influenza cases, 50.7% were 65 years of age or older, and 52.0% of children and 95.7% of adults had underlying conditions; 44.9% overall had received influenza vaccine prior to hospitalization. Overall, 34.5% of HA cases received ICU care during hospitalization, 19.8% required mechanical ventilation, and 6.7% died. After including possible HA cases, prevalence among all influenza-associated hospitalizations increased to 1.3% and the adjusted rate increased to 1.5 per 100, 000 persons. Conclusions: Over 8 seasons, rates of HA influenza were low but were likely underestimated because testing was not systematic. A high proportion of patients with HA influenza were unvaccinated and had severe outcomes. Annual influenza vaccination and implementation of robust hospital infection control measures may help to prevent HA influenza and its impacts on patient outcomes and the healthcare system.